The impact of organizational integration in achieving entrepreneurial orientation - an analytical study of the opinions of a sample of individuals in Al-Kafeel General Investments Company - Sahar Abbas Hussain, (Iraqi Journal for Administrative Sciences, 2025)
Purpose:Statement the impact of Organizational identification in Entrepreneurship Orientation Entrance / methodology : It was Selection workers were in Al-kafel company for public investments in Karbala. Using a questionnaire for research based on metrics available in the literature and in line with the research environment after tested in the range of statistical techniques . Results /The presence of correlation and the significant effect of the Organizational identification & Entrepreneurship Orientation. . Originality/Value : The value of research in addressing the side of the accumulation of knowledge in the field of Organizational identification& foundations of Entrepreneurship Orientation. Keywords: Organizational identification, Entrepreneurship Orientation , Innovativeness, proactiveness, Autonomy, risk taking